Dissolved gas and dissolved inorganic nitrogen concentrations and isotopes during METEOR cruise M91 - Mark A Altabet; Patricia Grasse (PANGAEA, 2021)
Seawater samples for stable isotopes measurements of nitrate (δ15NO3-) and nitrite (δ15NO2-) were taken from the CTD/rosette. δ15NO3- and δ15NO2- samples were either preserved frozen or an azide treatment was applied depending on the nitrite concentration (Altabet et al., 2012; Bourbonnais et al., 2015; Hu et al., 2016). The isotopic composition of both N-species was measured using the Cd reduction/azide method (McIlvin and Altabet, 2005).